Associations of habitual glucosamine use with SARS‐CoV‐2 infection and hospital admission and death with COVID‐19: Evidence from a large population based cohort study. Issue 4 (11th April 2023) - Meng, Meijun; Wu, Yanjun; Sha, Weihong; Zeng, Ruijie; Luo, Dongling; Jiang, Rui; Wu, Huihuan; Zhuo, Zewei; Yang, Qi; Li, Jingwei; Leung, Felix W.; Duan, Chongyang; et al.
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic has led to a fundamental number of morbidity and mortality worldwide. Glucosamine was indicated to help prevent and control RNA virus infection preclinically, while its potential therapeutic effects on COVID‐19‐related outcomes are largely unknown. To assess the association of habitual glucosamine use with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection, hospital admission, and mortality with COVID‐19 in a large population based cohort. Participants from UK Biobank were reinvited between June and September 2021 to have SARS‐CoV‐2 antibody testing. The associations between glucosamine use and the risk of SARS‐CoV‐2 infection were estimated by logistic regression. Hazard ratios (HRs) and 95% confidence intervals (CIs) for COVID‐19‐related outcomes were calculated using COX proportional hazards model. Furthermore, we carried out propensity‐score matching (PSM) and stratified analyses. At baseline, 42 673 (20.7%) of the 205 704 participants reported as habitual glucosamine users. During median follow‐up of 1.67 years, there were 15 299 cases of SARS‐CoV‐2 infection, 4214 cases of COVID‐19 hospital admission, and 1141 cases of COVID‐19 mortality. The fully adjusted odds ratio of SARS‐CoV‐2 infection with glucosamine use was 0.96 (95% CI: 0.92–1.01). The fully adjusted HR were 0.80 (95% CI: 0.74–0.87) for hospital admission, and 0.81 (95% CI: 0.69–0.95) for mortality. The logistic regression and Cox proportional hazard analyses after PSM yielded consistent results. Our study demonstrated that habitual glucosamine use is associated with reduced risks of hospital admission and death with COVID‐19, but not the incidence of SARS‐CoV‐2 infection.